Pelatihan Pembuatan Laporan Keuangan Bagi Umkm Untuk Meningkatkan Transparansi Dan Efisiensi Bisnis - Citra Etika; El Vito Kumala; Rio Dermawantoro; Rahma Nur Anisa; Meta Priska Yulita (Universitas Sumatera Barat, 2024)
Small and Medium-sized Enterprises (SMEs) play a crucial role in Indonesia's economy, yet many SMEs owners, particularly in rural areas like Bulok Village, Kalianda District, South Lampung Regency, lack the knowledge to prepare proper financial reports. This community service activity aimed to provide these SMEs owners with the necessary understanding and skills in financial reporting. The training was conducted face-to-face over one day, focusing solely on theoretical aspects. Twenty participants attended, engaging actively in discussions and questions. Despite their initial unfamiliarity with financial reporting, the participants demonstrated significant improvement in understanding, particularly in differentiating various types of financial reports. The training method was adapted to address the participants' lack of prior knowledge, using simple explanations and analogies to ensure comprehension. Feedback indicated that the material was clearly and effectively communicated. The training successfully met its objectives, equipping participants with a better grasp of financial reporting's importance for their business management. Although no follow-up sessions are planned, the training is expected to have a lasting positive impact on the participants' ability to manage their business finances more effectively and systematically.